Improving the Positioning Accuracy of Acoustic Emission Events by Optimizing the Sensor Deployment and First Arrival Signal Picking - Yanlong Chen; Mingwei Zhang; Haoshuai Wu; Kai Zhang; Deyu Qian (IEEE Access, 2020)
Acoustic emission (AE) source location is an effective method used to reveal the deformation and damage characteristics of materials. Improving the positioning accuracy of AE events is extremely important for both experimental research and engineering practice. An experiment was performed on a standard rock specimen to investigate the key factors that affect the positioning accuracy of an AE event, such as the computational combinations and spatial layout of the sensors and the picking accuracy of the first arrival signal. The results show that as the number of sensors involved in the positioning calculation increases, both the maximum and average positioning errors clearly decrease, and the positioning accuracy increases. Meanwhile, a better result is achieved when the number of sensors involved in the positioning calculation reaches three-fourths of the total number of monitoring sensors used. Under this condition, both the minimum positioning error and the error dispersion are sufficiently low, and the reliability of the positioning results is greatly improved. Furthermore, when different types of and deviations in the first arrival signal are used for the location calculation of the same AE event, the positioning results are quite different, and large errors are found. Finally, the accurate positioning of an AE event is realized by adjusting the number of sensors and improving the picking accuracy of the first arrival time of the signal. The maximum reduction in the positioning error achieved is 96.62%, and the minimum reduction is 57.61%. Hence, the positioning error decreases significantly. The investigation results can provide an important reference for the precise positioning of AE events involved in experimental research and engineering.